Structural and functional deficits in a neuronal calcium sensor-1 mutant identified in a case of autistic spectrum disorder. - Mark T W Handley; Lu-Yun Lian; Lee P Haynes; Robert D Burgoyne (PLoS ONE)
Neuronal calcium sensor-1 (NCS-1) is a Ca(2+) sensor protein that has been implicated in the regulation of various aspects of neuronal development and neurotransmission. It exerts its effects through interactions with a range of target proteins one of which is interleukin receptor accessory protein like-1 (IL1RAPL1) protein. Mutations in IL1RAPL1 have recently been associated with autism spectrum disorders and a missense mutation (R102Q) on NCS-1 has been found in one individual with autism. We have examined the effect of this mutation on the structure and function of NCS-1. From use of NMR spectroscopy, it appeared that the R102Q affected the structure of the protein particularly with an increase in the extent of conformational exchange in the C-terminus of the protein. Despite this change NCS-1(R102Q) did not show changes in its affinity for Ca(2+) or binding to IL1RAPL1 and its intracellular localisation was unaffected. Assessment of NCS-1 dynamics indicated that it could rapidly cycle between cytosolic and membrane pools and that the cycling onto the plasma membrane was specifically changed in NCS-1(R102Q) with the loss of a Ca(2+) -dependent component. From these data we speculate that impairment of the normal cycling of NCS-1 by the R102Q mutation could have subtle effects on neuronal signalling and physiology in the developing and adult brain.